2022
DOI: 10.1001/jamanetworkopen.2022.34168
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Characteristics Associated With Opioid Overdose Following Buprenorphine Taper

Abstract: ImportanceRetention in buprenorphine therapy is associated with a lower risk of opioid overdose. Nevertheless, many patients discontinue treatment, and there is limited evidence to guide buprenorphine tapering.ObjectiveTo understand what prescribing characteristics are associated with opioid overdose following buprenorphine taper.Design, Setting, and ParticipantsThis is a population-based, retrospective, cohort study of adults who were maintained on buprenorphine for at least 60 days and underwent a buprenorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…We selected a 14-day interval because an interruption in treatment of this length would warrant reinitiating treatment, and has been used previously. 20,21 Among those who discontinued OAT, we defined the date of discontinuation as the dispensing date of the final prescription plus the day supply. We followed each person for up to 3 years, until the first of OAT discontinuation, switch between methadone and buprenorphine/naloxone, death, or December 31, 2019, whichever occurred first.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected a 14-day interval because an interruption in treatment of this length would warrant reinitiating treatment, and has been used previously. 20,21 Among those who discontinued OAT, we defined the date of discontinuation as the dispensing date of the final prescription plus the day supply. We followed each person for up to 3 years, until the first of OAT discontinuation, switch between methadone and buprenorphine/naloxone, death, or December 31, 2019, whichever occurred first.…”
Section: Discussionmentioning
confidence: 99%
“…Our primary outcome was time to treatment discontinuation, defined as missing a minimum of 14 consecutive days of the OAT initially prescribed, regardless of whether dose was tapered. We selected a 14-day interval because an interruption in treatment of this length would warrant reinitiating treatment, and has been used previously 20,21 . Among those who discontinued OAT, we defined the date of discontinuation as the dispensing date of the final prescription plus the day supply.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, three clinical trials reported higher relapse rates after completing methadone taper, ranging from 53.1% to 66.7% of individuals relapsed by the first month and 61.1% to 89.2% by the sixth month after taper completion 1 16–18. Furthermore, the ideal duration of stability before a taper is initiated may be related to clients’ clinical course, severity, adherence to OAT treatment and other social factors such as family support and financial status, housing status and neighbourhood environment 1 4 19–23. A retrospective cohort study with 8996 clients who discontinued buprenorphine treatment found that individuals who were retained in treatment for 15–18 months had a lower probability of emergency department visits, hospitalisations and filling opioid prescriptions in the 6 months following discontinuation than individuals retained for 6–9 months 24.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from BC, Canada, and Guangdong, China, both demonstrated that more gradual and staggered dose decreases increased the likelihood of taper completion 4 26. A retrospective cohort study of 5774 individuals undergoing a buprenorphine taper reported that regardless of the tapering strategy, however, the time to taper initiation demonstrated an independent effect on the likelihood of successful taper completion,20 in contrast to the prior study from BC involving methadone 4. The independent effect of when the OAT taper is initiated or the possible effects of OAT medication type in the treatment course thus remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These patients could benefit initially from a gradual opioid tapering using quick onset and short‐acting opioids without known addiction properties. Whereas buprenorphine taper is clinically used, it takes very long time to taper down due to it long half‐life and it is associated with post‐taper overdose death, and buprenorphine itself is addictive 9 . In the future drug development for addiction therapy, short‐acting regimen for an easy taper down or taper off opioids should be explored.…”
mentioning
confidence: 99%